Design and Implementation of a Secure IoT-Blockchain Integrated System for Real-Time Attendance Verification - Ramanov Muxiddin Xamrobekovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In the digital era, traditional attendance systems remain vulnerable to manipulation, inefficiency, and lack of trust. This paper presents the design and implementation of a hybrid system that integrates Internet of Things (IoT) devices with blockchain technology to deliver a secure, real-time attendance tracking solution. Using RFID/NFC sensors and a backend integrated with TrustContract (TrustMe.uz), attendance events are automatically recorded and verified on a tamper-proof blockchain ledger. This ensures both operational efficiency and legal enforceability of records. Real-world deployment and testing demonstrate the system's potential for scalability and nationwide adoption, particularly in developing digital infrastructures like Uzbekistan.